THE INFLUENCE OF INVESTMENT ATTITUDES, SUBJECTIVE NORMS, SOCIAL MEDIA, AND THE BANDWAGON EFFECT ON STUDENTS’ INVESTMENT INTEREST IN THE CAPITAL MARKET - Adi, Faisal Satrio; Kusuma, Poppy Dian Indira; Farida, Yusriati Nur (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study aims to examine whether attitudes toward investment, subjective norms, social media, and the bandwagon effect influence students’ interest in investing in the capital market. This research employs a quantitative approach. The research subjects consist of active students of the Faculty of Economics and Business at Universitas Jenderal Soedirman, cohorts 2017 to 2019. The total population in this study is 229 students. The sampling technique used is simple random sampling, with the sample size determined using the Slovin formula, resulting in 70 respondents. Data analysis techniques include data quality testing, descriptive statistical analysis, classical assumption tests, and multiple regression analysis. The results show that: (1) attitudes toward investment have a positive effect on increasing students’ investment interest in the capital market; (2) subjective norms do not have a significant effect on increasing students’ investment interest in the capital market; (3) social media has a positive effect on increasing students’ investment interest in the capital market; and (4) the bandwagon effect has a positive effect on increasing students’ investment interest in the capital market. The implications of this study are expected to contribute to the development of knowledge in the field of financial accounting, particularly related to investment. Future research on internal factors may be expanded by analyzing other causal factors that influence and are associated with investment interest. Consequently, students’ understanding and literacy in economics—especially in accounting, finance, and investment—can be enhanced, along with their economic behavior in managing personal finances in accordance with current economic conditions. Furthermore, this study is expected to assist students, lecturers, faculties, and universities in providing investment-related information, facilitating access and communication through collaboration between universities and securities companies, stock exchanges, and other stakeholders involved in investment activities. Students are expected to gain a deeper understanding of investment, make effective use of time to enhance investment knowledge, and avoid consumptive lifestyles by developing the habit of investing with minimal initial capital. Through capital market seminar and training programs organized by universities, it is expected that students will develop positive perceptions of investment, thereby fostering their interest in starting stock investments in the capital market.